Respuesta :

Answer:

g(3a – 6) = a - 4

Step-by-step explanation:

g(x) = 1/3x - 2

g(3a – 6) = 1/3(3a – 6) - 2

= a - 2 - 2

= a - 4

Answer:

g(3a - 6) = a - 4

Step-by-step explanation:

If you start with g(x) = 1/3 x - 2

Then whatever x = on the left, must take on the value on the right.

g(3a - 6) = 1/3 (3a - 6) - 2     Notice the x is gone and 3a - 6 has taken it's place.

Now you must distribute the 1/3 for both 2a and 6

g(3a - 6) = 1/3 * 3a - 1/3 * 6 - 2

g(3a - 6) = a - 2 - 2

g(3a - 6) = a - 4